2013
DOI: 10.1073/pnas.1317113110
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ ionophore A23187 can make mouse spermatozoa capable of fertilizing in vitro without activation of cAMP-dependent phosphorylation pathways

Abstract: Ca2+ ionophore A23187 is known to induce the acrosome reaction of mammalian spermatozoa, but it also quickly immobilizes them. Although mouse spermatozoa were immobilized by this ionophore, they initiated vigorous motility (hyperactivation) soon after this reagent was washed away by centrifugation. About half of live spermatozoa were acrosome-reacted at the end of 10 min of ionophore treatment; fertilization of cumulus-intact oocytes began as soon as spermatozoa recovered their motility and before the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 45 publications
(46 reference statements)
7
115
0
Order By: Relevance
“…Under the physiological condition in vivo, acrosome reaction occurs by fusion of the cytoplasmic membrane in sperm head and the underlying outer acrosomal membrane [32], which is a necessary step for fertilization. It is well-known that calcium ionophore A23187 can induce acrosome reaction in vitro [33]. In this study, we observed that AMPK phosphorylation occurred during in vitro induction of acrosome reaction (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Under the physiological condition in vivo, acrosome reaction occurs by fusion of the cytoplasmic membrane in sperm head and the underlying outer acrosomal membrane [32], which is a necessary step for fertilization. It is well-known that calcium ionophore A23187 can induce acrosome reaction in vitro [33]. In this study, we observed that AMPK phosphorylation occurred during in vitro induction of acrosome reaction (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…However, other cAMP-binding proteins have been proposed to participate in some of the processes 27 . In addition, cAMP and its targets regulate a variety of capacitation-induced signaling events including: 1) membrane lipid remodeling 28,29 ; 2) hyperpolarization of the sperm plasma membrane 30 ; 3) increase in intracellular pH 30,31,32,33 ; 4) increase in intracellular Ca 2+ 34 ; and 5) increase in protein tyrosine phosphorylation 35 . Although one important aspect of the sperm capacitation process is the preparation of the sperm to undergo a physiologically relevant exocytotic reaction known as acrosome reaction, the acrosome reaction per se is usually considered outside of the capacitation process 36 .…”
Section: Role Of Camp In Sperm Functionmentioning
confidence: 99%
“…To answer these questions, we investigated the effect of NaF on sperm motility and motion kinematic parameters. The intracellular Ca 2+ and ATP concentrations were measured to observe time-dependent occurrence of several fundamental events in spermatozoa, where Ca 2+ and ATP extensively involved in almost every step (Tateno et al, 2013;Krapf et al, 2014;Rahman et al, 2014a). We also evaluated capacitation status of spermatozoa and alterations protein kinase-A (PKA) activity and protein tyrosine phosphorylation patterns that regulate intracellular changes (Naz & Rajesh, 2004;Visconti, 2009;Kwon et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%